Efficient and Versatile Interconnection Layer by Solvent Treatment of PEDOT:PSS Interlayer for Air‐Processed Organic Tandem Solar Cells. Issue 23 (25th October 2016) - Prosa, Mario; Tessarolo, Marta; Bolognesi, Margherita; Cramer, Tobias; Chen, Zhihua; Facchetti, Antonio; Fraboni, Beatrice; Seri, Mirko; Ruani, Giampiero; Muccini, Michele
Abstract : A robust and efficient interconnection layer (ICL) based on low conductive poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) and ZnO nanoparticles is implemented in a solution‐air‐processed, blade coated inverted polymer tandem solar cell. The commercial PEDOT:PSS (Heraeus Clevios P VP Al 4083) is modified with a fluorosurfactant to allow its deposition onto any hydrophobic active layer surface. However, this method alters the electrical and energetic properties of the PEDOT:PSS thus affecting the interface with the ZnO layer, responsible for an inefficient ICL and poorly performing tandem devices. The ohmic contact at the PEDOT:PSS/ZnO interface is successfully optimized through a simple solvent treatment of the PEDOT:PSS film surface, leading to tandem devices with power conversion efficiencies (PCEs) improved by more than 50% compared to the untreated reference system. The reported method is an easy and versatile approach to optimize the functionality of the PEDOT:PSS/ZnO ICL of inverted multijunction devices, applicable onto any organic active layer and compatible with a roll‐to‐roll production line. Abstract : Air processed inverted tandem solar cells are fabricated using surfactant modified poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) and ZnO as interconnection layer (ICL). Limitations at the PEDOT:PSS/ZnO interface, induced by the presence of surfactant in the PEDOT:PSS film, are solved by solvent‐treating the surface of the PEDOT:PSS layer. This results a versatile and scalable approach for processing the ICL of organic multijunction devices.